2002
DOI: 10.1098/rspb.2001.1877
|View full text |Cite
|
Sign up to set email alerts
|

A Gondwanan origin of passerine birds supported by DNA sequences of the endemic New Zealand wrens

Abstract: Zoogeographic, palaeontological and biochemical data support a Southern Hemisphere origin for passerine birds, while accumulating molecular data suggest that most extant avian orders originated in the midLate Cretaceous. We obtained DNA sequence data from the nuclear c-myc and RAG-1 genes of the major passerine groups and here we demonstrate that the endemic New Zealand wrens (Acanthisittidae) are the sister taxon to all other extant passerines, supporting a Gondwanan origin and early radiation of passerines. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
281
5

Year Published

2002
2002
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 322 publications
(305 citation statements)
references
References 34 publications
15
281
5
Order By: Relevance
“…The bootstrap consensus tree (Fig. 2) indicated that the New Zealand wren A. chloris, member of a group sometimes considered suboscine, was sister to ah other passerines, consistent with previous studies using sequence data (Barker et al, 2002;Ericson et al, 2002). Within the remainder of the passerines, the suboscines and oscines formed monophyletic groups.…”
Section: Phylogenetic Analyses•nuclearsupporting
confidence: 86%
“…The bootstrap consensus tree (Fig. 2) indicated that the New Zealand wren A. chloris, member of a group sometimes considered suboscine, was sister to ah other passerines, consistent with previous studies using sequence data (Barker et al, 2002;Ericson et al, 2002). Within the remainder of the passerines, the suboscines and oscines formed monophyletic groups.…”
Section: Phylogenetic Analyses•nuclearsupporting
confidence: 86%
“…Besides the two specimens mentioned above, they include a nearly complete Wieslochia weissi from Germany Manegold 2004, 2006a), an articulated wing (Mayr and Manegold 2006b), and several dozen isolated wing bones (Manegold 2008;Mourer-Chauviré et al 1989). Outside Europe, Paleogene remains of possible passerines are known only from the early Eocene of Australia (Boles 1995(Boles , 1997, which agrees with the theory of the Southern Hemisphere origin of passerines based on DNA sequences (Ericson et al 2002; see also Mayr 2013).…”
Section: Introductionsupporting
confidence: 62%
“…Recent molecular evidence shows that passerines are as old as the major non-passerine groups and probably date well back in the Cretaceous, in the Gondwanan region (e.g. Ericson et al, 2002), and so both groups may well have been subjected to similar forces, as suggested by Crowe & Crowe (1982). In addition, it would appear that, especially in the rain forests, both non-passerines and passerine species are generally much older than was previously thought (Roy et al, 2000).…”
Section: Discussionmentioning
confidence: 93%